A self-efficacy questionnaire regarding leisure time physical activity: Psychometric properties among Iranian male adolescents - Mohammad Hadi Abasi; Ahmad Ali Eslami; Fatemeh Rakhshani; Mansoor Shiri (Wolters Kluwer Medknow Publications, 2016)
Background: Attention to different aspects of self-efficacy leads to actual evaluation of self-efficacy about physical activity. This study was carried out in order to design and determine psychometric characteristics of a questionnaire for evaluation of self-efficacy about leisure time physical activity (SELPA) among Iranian adolescent boys, with an emphasis on regulatory self-efficacy. Materials and Methods: This descriptive-analytic study was conducted in 734 male adolescents aged 15-19 years in Isfahan. After item generation and item selection based on review of literature and other questionnaires, content validity index (CVI) and content validity ratio (CVR) were determined and items were modified employing the opinions of expert panel (N = 10). Comprehensibility of the questionnaire was determined by members of target group (N = 35). Exploratory factors analysis (EFA) was operated on sample 1 (N1 = 325) and confirmatory factors analysis (CFA) on sample 2 (N2 = 347). Reliability of SELPA was estimated via internal consistency method. Results: According to EFA, barrier self-efficacy and scheduling self-efficacy are the two main aspects of SELPA with the total variance of 65%. The suggested model was confirmed by CFA and all fitness indices of the corrected model were good. Cronbach's alpha was totally estimated as 0.89 and for barrier and scheduling self-efficacy, it was 0.86 and 0.81, respectively. Conclusions: The results provide some evidence for acceptable validity and reliability of SELPA in Iranian adolescent boys. However, further investigations, especially for evaluation of predictive power of the questionnaire, are necessary.